Therapeutic approaches to enhance natural killer cell cytotoxicity - Stenger, Terran D.; Miller, Jeffrey S. (Frontiers in Immunology, 2024)
Enhancing the cytotoxicity of natural killer (NK) cells has emerged as a promising strategy in cancer immunotherapy, due to their pivotal role in immune surveillance and tumor clearance. This literature review provides a comprehensive overview of therapeutic approaches designed to augment NK cell cytotoxicity. We analyze a wide range of strategies, including cytokine-based treatment, monoclonal antibodies, and NK cell engagers, and discuss criteria that must be considered when selecting an NK cell product to combine with these strategies. Furthermore, we discuss the challenges and limitations associated with each therapeutic strategy, as well as the potential for combination therapies to maximize NK cell cytotoxicity while minimizing adverse effects. By exploring the wealth of research on this topic, this literature review aims to provide a comprehensive resource for researchers and clinicians seeking to develop and implement novel therapeutic strategies that harness the full potential of NK cells in the fight against cancer. Enhancing NK cell cytotoxicity holds great promise in the evolving landscape of immunotherapy, and this review serves as a roadmap for understanding the current state of the field and the future directions in NK cell-based therapies.